Horseshoe Kidney Complicated by Xanthogranulomatous Pyelonephritis in a Young Girl: A Case Report and Review of the Literature - Musayev, Jamal; Sholan, Rashad; Hasanov, Adalat; Rustamov, Rizvan (Acta medica (Hradec Kralove), 2021)
The cases of horseshoe kidney presented by xanthogranulomatous pyelonephritis are very rare. In this study, the case of XGP developing in HSK in a young female patient was presented due to its rare incidence and the previously reported cases were reviewed, as well. The patient, who has end-stage renal disease and was under treatment, admitted to the clinic for preemptive kidney transplantation. Bilateral open en bloc nephrectomy was performed before the kidney transplantation. The histopathological examination of the specimen was reported as XGP. Eight months later, living-donor organ transplantation was performed to the patient with the kidney obtained from her father. XGP can present as a complication of HSK. Moreover, HSK may rarely be manifested by end-stage renal disease in young patients. In such cases, who would undergo kidney transplantation, it is important to examine the HSK in detail and perform bilateral nephrectomy to prevent complications after transplantation.
Keywords: Living Donors; fúze ledvin; Kidney Failure, Chronic; Humans; xanthogranulomatous pyelonephritis; žijící dárci; Female; Fused Kidney; Pyelonephritis, Xanthogranulomatous; lidé; transplantace ledvin; ženské pohlaví; chronické selhání ledvin; Kidney Transplantation; xantogranulomatózní pyelonefritida; horseshoe kidney; Nephrectomy; nefrektomie; bilateral nephrectomy; end-stage renal disease